CARDIOVASCULAR COMPLICATIONS OF OBSTRUCTIVE SLEEP APNEA SYNDROME: FOCUS ON MYOCARDIAL REPOLARIZATION ABNORMALITIES - Zhdan V. M.; Katerenchuk O. I.; Ivanytskyi I. V.; Kyrian O. A.; Haymenova G. S. (Eastern Ukrainian Medical Journal, 2020)
Obstructive sleep apnea syndrome is a risk factor for cardiovascular diseases occurrence and progression. The leading pathophysiological mechanism is hyperactivation of the sympathetic autonomic nervous system. Changes in myocardial repolarization processes may serve as an early marker of increased risk for myocardial ischemia in individuals without cardiovascular diseases. Also, it is unclear how the treatment of obstructive sleep apnea syndrome can influence autonomic regulation and myocardial repolarization.The objective of the study was to evaluate the relationship of autonomic dysfunction and myocardial repolarization abnormalities caused by obstructive sleep apnea syndrome and its changes after the treatment of underlying condition.Results: 15 patients with obstructive sleep apnea syndrome of mild and moderate degree were enrolled into the study group. The control group was formed from healthy individuals. An increased tonic sympathetic activity was observed in the study group. It was associated with increased values of the T-wave symmetry standard quadratic deviation index. Treatment of obstructive sleep apnea syndrome by otorhinolaryngological procedures (septoplasty, uvulopalatoplasty, removal of nasal polyps, uvulopalatapharyngoplasty) resulted in improvement of tonic autonomic regulation (in terms of sinus rhythm variability) and normalization of myocardial repolarization that were evaluated in 3 months after treatment.Conclusions. Tonic sympathetic hyperactivation changes the processes of myocardial repolarization in patients with obstructive sleep apnea syndrome. Treatment of obstructive sleep apnea syndrome with otorhinolaryngological procedures improves autonomic regulation and myocardial repolarization processes.